2012
DOI: 10.1111/j.1365-2559.2012.04326.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1, E‐cadherin and beta‐catenin expression in FIGO Stage IA cervical squamous carcinoma: diagnostic value and evidence for epithelial–mesenchymal transition

Abstract: Most superficially invasive cervical squamous carcinomas show immunophenotypical changes consistent with EMT. These alterations, particularly cyclin D1 expression, may be useful diagnostically. Similar changes in CIN 3 lesions may indicate the acquisition of increased invasive potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 37 publications
3
21
0
Order By: Relevance
“…Our results have demonstrated that the loss of β -catenin expression strongly characterises the transition from cells at the central tumour to invasive nests or isolated tumour cells in elderly patients with VSCC having no HPV infection (Table 7). Similar findings have been recorded in cervical squamous carcinoma, in which there was reduced β -catenin immunoexpression in many of infiltrative tumour cells, particularly at the tumour–stromal interface (Koay et al , 2012). In the present study, loss of β -catenin expression was statistically associated with FIGO stages III and IV, and Cox regression model also demonstrated that loss β -catenin expression was an independent factor associated with poor survival (Table 8).…”
Section: Discussionsupporting
confidence: 80%
“…Our results have demonstrated that the loss of β -catenin expression strongly characterises the transition from cells at the central tumour to invasive nests or isolated tumour cells in elderly patients with VSCC having no HPV infection (Table 7). Similar findings have been recorded in cervical squamous carcinoma, in which there was reduced β -catenin immunoexpression in many of infiltrative tumour cells, particularly at the tumour–stromal interface (Koay et al , 2012). In the present study, loss of β -catenin expression was statistically associated with FIGO stages III and IV, and Cox regression model also demonstrated that loss β -catenin expression was an independent factor associated with poor survival (Table 8).…”
Section: Discussionsupporting
confidence: 80%
“…They also showed gradual increase of cyclin D1 expression with progression from dysplasia to invasive cancers, which is agreement with our result. This slight increase of cyclin D1 in cervical cancer may be associated with the involvement of cyclin D1 in the acquisition of invasive potential [38]. Recent studies have revealed the specific function of cyclin D1 in cell migration [3940].…”
Section: Discussionmentioning
confidence: 99%
“…EMT, a highly conserved biological process leading to the induction of invasive growth and metastasis formation, has intensively been studied and is described for multiple cancers, including cervical cancer [2628]. On the molecular level, EMT is marked by an increased expression of vimentin, a reorganization of the actin cytoskeleton and downregulation of E-cadherin with a switch to higher levels of N-cadherin [29, 30].…”
Section: Introductionmentioning
confidence: 99%